Microsatellite Typing and Antifungal Susceptibility of Candida glabrata Strains Isolated From Patients With Candida Vaginitis - Kiasat, Neda; Rezaei-Matehkolaei, Ali; Mahmoudabadi, Ali Zarei (Frontiers in Microbiology, 2019)
Vulvovaginal candidiasis (VVC) is a yeast infection with a global distribution and millions of dollars are annually spent for its diagnosis and treatment. Recently, Candida glabrata with different degrees of antifungal resistance has been considered as the second common cause of vaginal infections. The aim of the present study was to determine the antifungal susceptibility and molecular epidemiology profiles of C. glabrata isolates from patients with VVC. Sixty-one C. glabrata isolates were examined for antifungal susceptibility using the EUCAST broth microdilution method. Moreover, microsatellite length polymorphism was used for typing the C. glabrata isolates using six microsatellite markers. Overall, 13%, 3.3%, and 0% of the isolates were non-wild types to itraconazole, posaconazole, and voriconazole, respectively. Sixty (98.4%) isolates were intermediate phenotype to fluconazole and only one isolate was fluconazole-resistant. Microsatellite length polymorphism with a discriminatory power of 0.964 identified 35 distinct types and 24 singleton genotypes. The assessment of the population genetic structure revealed that the non-wild-type population had a moderate genetic differentiation compared to the wild type population (FST = 0.1457). It was also found that the most common genotypes were G27 (8 strains), G12 (6 strains), and G4 (5 strains). We found that 8 strains were resistant/non-wild phenotype to itraconazole. 5 out of 8 (62.5%) resistant/non-wild phenotype strains correlated to predominant genotype (GT27) and the rest of them belonged to GT11 (12.5%), GT29 (12.5%), and GT28 (12.5%). The current research is the first molecular epidemiology study in the southwest of Iran and demonstrates the antifungal susceptibility profiles of C. glabrata in it. This study shows a wide range of the genetic diversity of C. glabrata (35 different genotypes) from VVC in the southwest of Iran. The majority of the non-wild isolates had a dominant genotype or genotypes related to this dominant genotype (clonal cluster one).